Multi‐source and multi‐relay cooperative system based on compressed sensing. Issue 22 (8th October 2015) - Fu, Xiaomei; Cui, Yangran
Abstract : In this Letter, the compressed sensing is introduced into multi‐source and multi‐relay cooperative system. The compressed process is executed by the linear combination in the air of the transmitted signal. The cooperative compressed sensing and amplify‐and‐forward (CCS‐AF) scheme is investigated. It is firstly proved that CCS‐AF transmission matrix can be regarded as the measurement matrix. The channel capacity is improved greatly by cooperative compression. The numerical results validate the effectiveness of the model and the scheme.